2014
DOI: 10.1176/appi.ajp.2014.12111402
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcome Following In Utero Exposure to Lithium: A Prospective, Comparative, Observational Study

Abstract: Lithium treatment in pregnancy is associated with a higher rate of cardiovascular anomalies. Women who are treated with lithium during organogenesis should undergo fetal echocardiography and level-2 ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 32 publications
6
79
1
3
Order By: Relevance
“…Another study on adverse birth outcome following lithium exposure in pregnancy identified 83 lithium-exposed pregnancies among women who contacted the Israeli Teratology Information Service between 1999 and 2010. 51 Both studies support our findings that lithium is still used by pregnant women, but rarely.…”
Section: Psychotropic Medication Prescribed Before During and After supporting
confidence: 83%
See 1 more Smart Citation
“…Another study on adverse birth outcome following lithium exposure in pregnancy identified 83 lithium-exposed pregnancies among women who contacted the Israeli Teratology Information Service between 1999 and 2010. 51 Both studies support our findings that lithium is still used by pregnant women, but rarely.…”
Section: Psychotropic Medication Prescribed Before During and After supporting
confidence: 83%
“…93 The Swedish study discussed previously 48 included 79 women using lithium in pregnancy and identified four children with congenital cardiac malformations equivalent to a prevalence rate of 5.1% (95% CI 1.4% to 12.5%). A recent study 51 based on 183 women exposed to lithium during pregnancy who contacted the Israeli Teratology Information Service also suggests lithium treatment in pregnancy is associated with a higher rate of cardiovascular anomalies. We had only 28 mother-child pairs in our study in which the mother had been prescribed lithium in pregnancy and were therefore unable to conduct further analysis on congenital malformations.…”
Section: Lithiummentioning
confidence: 99%
“…50,51 An often reported significant effect of lithium therapy is birth of large for gestational age (LGA) infants, with affected babies weighing an average of ∼100 gm heavier than their nonexposed counterparts. 51,52 Neonatal hypotonicity or "floppy baby" syndrome is also a noted adverse outcome of neonatal lithium toxicity, often resolving completely after the drug clearance. 9,40 There are no data that support or describe any detrimental long-term behavioral or developmental effects on neonates of mothers treated with lithium.…”
Section: No Medical Treatmentmentioning
confidence: 99%
“…40 If a woman continues Lithium therapy during conception and pregnancy, it is recommended that she undergo a fetal echocardiography in addition to her routine anatomy ultrasound. 52 In a well-controlled BPD patient in whom expectant management is appropriate, either medication tapering or drug discontinuation during the first trimester is a reasonable choice. Lithium is excreted into breast milk, and the infant serum levels are near therapeutic levels.…”
Section: No Medical Treatmentmentioning
confidence: 99%
“…21 In two uncontrolled cohort studies of lithium-exposed pregnancies, no cardiac malformations were detected in the 82 newborns examined 22,23 ; another uncontrolled study showed four mild cardiac defects in 79 exposed infants. 24 Four controlled cohort studies (involving between 59 and 138 lithiumexposed pregnancies) [25][26][27][28] showed conflicting results. Therefore, women with bipolar disorder who are of childbearing age and are planning to become pregnant have to balance the risks and benefits of treatment continuation on the basis of limited and conflicting evidence regarding the safety of lithium for the developing fetus.…”
mentioning
confidence: 99%